Abduction in Observational and in Theoretical Sciences. Some Examples of IBE in Palaeontology and in Cosmology - Rivadulla Rodríguez, Andrés (Revista de Filosofía, 2015)
Contrary to the view maintained by many philosophers that science employs the deductive testing of hypotheses, observational natural sciences such as paleoanthropology and the earth sciences apply a scientific methodology consisting in the proposal of hypotheses which are best fitted to the available empirical data, i.e. which best explain the data. Observational natural sciences are predominantly empirical. They are grounded in observation, and they do not implement any Popperian deductive testing of hypotheses. Theoretical natural sciences such as mathematical physics also apply inference to the best explanation for the introduction of significant concepts and hypotheses. The aim of this paper is to demonstrate that in contemporary science, the use of abductive reasoning continues to be as effective as ever.
Keywords: abduction; observational sciences; theoretical sciences; paleoanthropology; cosmology